BAI’ ISTIJROR PERSPEKTIF IMAM SYAFI’I DAN IMAM MA̅LIK DI DALAM KITAB AL-UMM DAN AL-MUWATTHA’ - Ma’arif, Ma'arif; Bashori, Akmal (At-Ta’awun: Jurnal Mu’amalah dan Hukum Islam, 2023)
This article presents a comparison of two great imams in the world, namely Imam Syafi'i and Imam Malik, regarding bai' istijror. there are opinions, istinbat and also arguments related to the problem. Bai' istijror is taking an item that is purchased little by little over a period of time. The research results show that there are significant differences between the opinions of Imam Syafi'i and Malik. Imam Syafi'i said that bai' istijror should not be based on the evidence of the Koran and hadith. Meanwhile, Imam Malik said that bai’ istijror is permitted on the basis of istinbat from the Koran and hadith as well. Even though they both rely on the Al-Qur'an and hadith, the sources of the verses and hadith are different so their opinions are different.